PERANCANGAN CHATBOT UNTUK PELAYANAN INFORMASI AKADEMIK DI UNIVERSITAS ESA UNGGUL KAMPUS BEKASI - Adrian, Adrian; Herwanto, Agus; Aryani, Diah; Yulhendri, Yulhendri (CV SWA Anugerah, 2025)
Advances in information technology encourage educational institutions to adopt digital solutions to improve service efficiency. Esa Unggul University Bekasi is faced with the challenge of providing fast, accurate, and responsive information services to meet the needs of its students. This study focuses on the development of an automated chatbot based on Artificial Intelligence (AI) by utilizing Large Language Models (LLM) integrated with LangChain. This chatbot is designed to optimize academic and administrative information services, such as class schedules, academic guidance, and other administrative services. This system is designed to provide responses to various general student questions, including information related to filling out KRS, payments, and academic procedures. LangChain integration allows the chatbot to handle more complex interactions with a deeper understanding of user needs. In developing this system, the prototyping method is used to iterate design, development, and testing. Each iteration involves trials to improve the system based on user input. The results of the study show that the chatbot can provide responsive, relevant services and operate continuously with a high level of user satisfaction. This chatbot is expected to be able to improve the efficiency of information services for students, lighten the workload of administrative staff, and support the improvement of service quality at Esa Unggul University Bekasi.